Improving Teacher Resilience: Tackling Burnout Through Cognitive Ergonomics - Shofia, Alima; Sarianti, Kiki; Putri, Ranti Mustika; Desti, Yolanda; Rosalina, Desi; Fikrina, Aulia; Syafriani, Oza; Triha, Hadigufri; Gultom, Angga Wibowo; Amiszalina, Dea; Reki, Reki; Zazqia, Zilva Putri; Zahwa, Zahwa (Universitas Negeri Gorontalo, 2025)
This community service initiative, conducted by the Universitas Adzkia team at SD Negeri 15 Banuaran, aimed to address the issue of teacher burnout through a cognitive ergonomics approach. Burnout, characterized by mental, emotional, and physical exhaustion due to prolonged work stress, is a significant challenge faced by elementary school teachers. This seminar provided teachers with practical strategies to manage their cognitive workload, improve stress management, and create a more balanced work environment. The event was structured into three stages: preparation, implementation, and evaluation. During the implementation stage, teachers were introduced to cognitive ergonomics principles, including time management techniques, structured breaks, and the use of digital tools to reduce administrative burdens. The seminar also emphasized the importance of mental well-being and its impact on teaching quality and student learning. Feedback from participants indicated a high level of engagement and appreciation for the practical solutions offered. The success of this initiative highlights the importance of addressing teacher burnout through cognitive ergonomics, ultimately contributing to a healthier and more productive educational environment. This program serves as a model for future efforts to support teacher well-being and improve the quality of education in elementary schools.